Antiseizure monotherapy with imepitoin or phenobarbital in feline idiopathic epilepsy: a multicenter, single-blinded, randomized and placebo-controlled study - Charalambous, Marios; Tipold, Andrea; Volk, Holger A.; Knebel, Anna; Hünerfauth, Enrice-Ina; Von Klopmann, Thilo; Rupp, Stefan; Broeckx, Bart J. G.; Bhatti, Sofie F. M. (Frontiers in Veterinary Science, 2026)
In feline idiopathic epilepsy (IE), the options for antiseizure medications (ASMs) remain limited with no licensed drugs available in cats in Europe. This study aimed to evaluate and compare efficacy and safety of imepitoin and phenobarbital through a multicenter, single-blinded, randomized, placebo-controlled trial. A total of 37 cats were included in this study. The study treatment evaluation period lasted for 15 weeks. In the imepitoin group (n = 16), monthly seizure frequency was significantly reduced (p = 0.028; mean pre-treatment, 6.1; mean post-treatment, 3.0), though monthly seizure days (p = 0.055; mean pre-treatment, 4.4; mean post-treatment, 2.6) and number of cluster seizures (p = 1.00; mean pre-treatment, 0.9; mean post-treatment, 0.3) did not show significant changes. The responder rate (i.e., > 50% reduction in seizure frequency post treatment) was 62%. In the phenobarbital group (n = 10), treatment led to a significant reduction in monthly seizure frequency (p = 0.0026; mean pre-treatment, 8.1; mean post-treatment, 1.3) and seizure days (p = 0.0011; mean pre-treatment, 5.7; mean post-treatment, 0.5), but not in the number of cluster seizures (p = 0.82; mean pre-treatment, 1.3; mean post-treatment, 0.4). The responder rate was 90%. When compared, the reduction in seizure days was significantly higher for phenobarbital compared to imepitoin (p = 0.036), while no significant difference was found for seizure frequency (p = 0.13) and responder rate (p = 0.1). The time to first seizure event after starting treatment was significantly longer in the phenobarbital group compared to imepitoin (p = 0.047) and placebo (p = 0.0017), but not between imepitoin and placebo (p = 0.078). Adverse effects of mild to moderate severity were observed in 90% of the phenobarbital group (primarily sedation and ataxia) and 88% of the imepitoin group (primarily ataxia and increased ALT activity). Both phenobarbital and imepitoin demonstrated efficacy and safety in feline IE. While seizure frequency reduction did not differ significantly between treatments, phenobarbital was associated with a prolonged time to first seizure event after treatment initiation. Adverse effects were common but the majority of these effects were mild to moderate and transient.